Synthesis and Properties of Targeted Radioisotope Carriers Based on Poly(Acrylic Acid) Nanogels - Matusiak, Małgorzata; Rurarz, Beata P.; Kadłubowski, Sławomir; Wolszczak, Marian; Karczmarczyk, Urszula; Maurin, Michał; Kolesińska, Beata; Ulański, Piotr (Pharmaceutics, 2021)
Radiation crosslinking was employed to obtain nanocarriers based on poly(acrylic acid)—PAA—for targeted delivery of radioactive isotopes. These nanocarriers are internally crosslinked hydrophilic macromolecules—nanogels—bearing carboxylic groups to facilitate functionalization. PAA nanogels were conjugated with an engineered bombesin-derivative—oligopeptide combined with 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetate chelating moiety, aimed to provide selective radioligand transport. 4-(4,6-Dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium (DMTMM) toluene-4-sulfonate was used as the coupling agent. After tests on a model amine—p-toluidine—both commercial and home-synthesized DOTA-bombesin were successfully coupled to the nanogels and the obtained products were characterized. The radiolabeling efficiency of nanocarriers with 177Lu, was chromatographically tested. The results provide a proof of concept for the synthesis of radiation-synthesized nanogel-based radioisotope nanocarriers for theranostic applications.